Observation of Student and Teacher Behaviors during a Preliminary Active Playful Learning Intervention in Kindergarten Classrooms - Elias Blinkoff; Kimberly Turner Nesbitt; Roberta Michnick Golinkoff; Kathy Hirsh-Pasek (MDPI AG, 2024)
This study describes the implementation and effectiveness of an instructional coaching program for kindergarten teachers in the State of New Hampshire that was implemented in response to the State's play-based kindergarten mandate. Coaching was provided to 20 teachers from across the State. It focused on guided play, principles of how children learn, and the breadth of skills needed to achieve in the classroom and beyond. A novel adaptation of a classroom observation protocol measured classroom-, teacher-, and student-level behaviors predicted to change with coaching. Classroom-level results revealed a significant decrease in teacher-led direct instruction with a significant shift towards playful instruction, a possible precursor to guided play. Teachers did not change how students were organized in the classroom to promote this instruction, nor did they individually provide more inferential instruction or change their affect with this pedagogical shift. Yet, changes in student behaviors aligned with the coaching program. Students became more engaged with their learning, more active in their use of learning tools, and more communicative. These results offer valuable insights on the initial impacts of an instructional coaching program focused on guided play, how children learn, and what children learn. This study presents a feasible and effective model for professional development on play-based learning that is rooted in the science of learning and measurable in the classroom.